Violence Against Women: Sex Crimes and Prevention Ideas in Lithuania in 1918–1940 - Černevičiūtė, Sigita (History / Istorija, 2020)
Abstract. Tis article aims to investigate the legal defnition of sex crimes in interwar Lithuania, to reveal general tendencies in sex crimes against women and to present ideas in the academic community at that time for the prevention of such crimes. In researching the 1918–1940 criminal law, two groups of sex crimes are distinguished: sanguliavimas – illicit sexual intercourse and gašlavimas – lewd acts. Te analysis of sex crime statistical data and case law suggests that rape was the most common sexual crime against women in interwar Lithuania. Te prevention of sex crimes during that period has received little attention, although in the academic community eugenics ideas were discussed that suggested sterilization or castration for sex oﬀenders as a preventative and punitive measure, but this remained beyond the reach of the legal debate.